Additive manufacturing of multi-scale heterostructured high-strength steels. Issue 7 (3rd July 2021) - Tan, Chaolin; Chew, Youxiang; Duan, Ranxi; Weng, Fei; Sui, Shang; Ng, Fern Lan; Du, Zhenglin; Bi, Guijun
Abstract : Additive manufacturing (AM) enables the processing of heterogeneous materials with customised architectures to improve strength-ductility synergy. Herein, layerwise-heterostructured high-strength steels were processed by AM of two steel powders following the designed architectures. The fabricated high-strength steels with hierarchical heterogeneous characteristics at the layer, melt-pool and grain scales, exhibit good strength-ductility combination, reaching a strength of 1.32 GPa together with an elongation of 7.5%. The increased strength attributes to hetero-deformation induced strengthening. In-situ deformation monitoring reveals many unique deformation bands in heterostructure materials, which delays necking and improves ductility. The findings demonstrate a novel potential approach to circumvent material property trade-offs. GRAPHICAL ABSTRACT: IMPACT STATEMENT: Additively manufactured heterogeneous materials with controllable architectures achieved a good strength-ductility combination; the underlying strengthening mechanism and unique deformation behaviour are revealed.